Evaluación del efecto del nivel de fibra insoluble en la digestibilidad fecal en cuyes de ceba en la Quinta Experimental Punzara. - Jumbo Sari, Mariuxi Cecibel (2019)
The objective of this work was to evaluate the effect of the level of insoluble fiber in fecal digestibility in: dry matter, ash, fiber and to relate the bromatological composition of diets, in type 1 A (Cavia porcellus) guinea pigs, using Alfalfa is the main source of fiber. For this, 16 males were used, weighing between 700 and 800 grams. The experiment was carried out with a design in squares of Youden, developed in two moments, the diets were administered ad libitum, it was provided with an adaptation period of seven days, plus three days. Tas where the stool and weight were collected; with them (guinea pigs) but with a different diet level, moment two was executed. The bromatological analysis of: dry matter, ash, raw fiber of the applied diets of the excreted matter was performed, obtaining these results. In the digestibility of dry matter, no difference was detected between level (P = 0, 98) and level x moment (P = 0, 68) but it was related to the moment (P = 0,030); obtaining at the moment one 57, 2% to 66, 1% and moment two 49, 7% to 55, 9%. In the digestibility of ash, a difference was detected for the level (P = 0.001) and level moment (P = 0,060) and moment (P ≤ 0,001), where it was obtained; moment one 80% to 69, 7% and moment two 42, 6% to 75, 1%. In the digestibility of the raw fiber, a difference was found in the levels: moment (P = 0,070) and moment (P = <0,001); at time 1 the digestibility of the fiber was positive (29, 9% to 54, 7%); while moment two became negative (-62, 2% - 153%). In the correlation there is no significant difference of dry matter, ash, raw fiber with digestibility. Concluding in this investigation that the increase in the level of fiber did not affect the digestibility of dry matter, however it reduced the digestibility of the ash, and no relationship was detected between the digestibility with the composition with the research diets. Key words: Fiber, levels, digestibility and bromatological analysis